E-Learning Application Training for Junior High School and Madrasah Tsanawiyah Teachers in Manado City - Saini, Fadhlan; Halimah, Nur; Saud, Indah Wardaty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2022)
E-learning has always been a need for everyone. It develops to be utilized since Covid-19 attack. For this reason, many parties including Education attempts to involve applications in E-learning materials. Teachers, in particular required a lot of methods to apply teaching and learning materials through online materials. Within this case, this community service aims to train teachers in using and applying E-learning applications into the classroom. The following community service was accomplished in several schools located in Manado city, such as SMP Yapim, MTs Assalaam, Mts Al Muhajirin. The subjects were teachers from the following schools who have been teaching during covid-pandemic. This activity was held during one month. The results say that the teachers feel motivated, improved and getting understood to have an easier method to use E-learning application such as Edmodo and Google Classroom for their Classroom. The tools in those applications are useful, for instance, to perform an understanding about how to use formula in Math, how to express ideas in English, how to write an assignment in History, and how to learn sufficiently and properly. In the meantime, students are also conveyed grateful and enjoyable to use google classroom and Edmodo application. However, factors such as do not have and have limited smartphone, internet network, and the late to access the apps can be said as the problems found during the service by the team. Keywords: E-learning; Learning Applications, Junior High Schoool Teachers.